The Effectiveness of Yoga to Treat Premenstrual Syndrome in Young Women in the Archipelago - Kartika Sri Dewi Batubara; Rita Ridayani; Mardiah Mardiah (Aloha International Journal of Health Advancement (AIJHA), 2022)
Menstrual pain (dysmenorrhea) is pain felt before or during menstruation. Dysmenorrhea can be felt as a sensation of pain, cramps, and contractions in the uterus that are more than usual in intensity, frequency, and duration. Dysmenorrhea can occur even without problems in the reproductive organs. If not handled, This can be troublesome for the daily activities of young women. Several non-pharmacological therapies, such as yoga, attempted to overcome menstrual pain complaints in adolescent girls. Aim: Determining the effectiveness of the yoga method on the intensity of menstrual pain (dysmenorrhea) in adolescent girls on Kelong Island, Bintan Regency, in 2022. Method: This quantitative study uses a quasi-experimental one-group pre-test and post-test design for 35 samples. The design of this study used a pre-test before being given treatment; thus the results would be more accurate because it could compare the conditions before and after being given treatment. Data were collected from January to May 2022, then measured using a numerical scale. Data analysis using t-test dependent and independent. Results: Based on the statistical test in yoga treatment, the p-value is 0.000 (p